Determinasi Kepuasan Kerja Pegawai Puskesmas Palaran dan Implikasinya terhadap Mutu Pelayanan Kesehatan - Hasmariadi; Iwan M Ramdan; Blego Sedionoto (Jurnal Kesehatan Komunitas, 2026)
Job satisfaction among health center employees is crucial to healthcare quality. At Palaran Health Center, Samarinda City, the Community Satisfaction Index (IKM) was 77.38 (2023) and 77.55 (2024), while several 2024 Minimum Service Standard (SPM) coverages were far below the 100% target (under-five health services 65.83%, productive-age services 5.08%, older adult services 28.01%, and tuberculosis services 48.33%). This cross-sectional study involved 89 employees selected through total sampling. Data were collected using validated questionnaires (March–August 2025) and analyzed with the Kolmogorov–Smirnov, chi-square, multiple linear, and logistic regression tests. Results showed that promotion opportunities, supervision, and coworker relationships significantly influenced job satisfaction (p<0.05), while age, gender, education, length of service, and employment status were not significant. Logistic regression identified promotion opportunities (p=0.027; Exp(B)=0.159) and supervision (p=0.001; Exp(B)=0.202) as key predictors. Strengthening transparent promotion mechanisms and supportive supervision can enhance employee satisfaction and improve service quality.